A little princess [videorecording (DVD)] - Cuarón, Alfonso; Johnson, Mark, 1945 December 27-; LaGravenese, Richard; Chandler, Elizabeth; Bron, Eleanor; Cunningham, Liam; Matthews, Liesel; Burnett, Frances Hodgson, 1849-1924 (Warner Bros. Entertainment, Inc : Distributed by Warner Home Video, 2010)
After an exotic childhood spent in India, young Sara Crewe finds herself in New York, immured in Miss Minchin girls' school as her father sails off to World War I. When he is lost, a severe reversal of fortune ensues. Thanks to him, Sara knows that "All girls are princesses ... even if they wear rags or are not pretty or smart." Summoning all the qualities of a true princess, patrician and bereft Sara uses her creativity and sense of self-worth to spin magic dreams that sustain her during her time of trial.